DIPLOMASI EKONOMI KONSULAT JENDERAL REPUBLIK INDONESIA KOTA KINABALU DALAM PERDAGANGAN KOPI INDONESIA DI NEGERI SABAH, MALAYSIA - Amelia Rachmawati, Chisty Damayanti, GPH Dipokusumo (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2019)
ABSTRACTThis research described and analyzed the economic diplomacy of Republic ofIndonesia’s Consulate General in Kinabalu City in Indonesian coffee trading inSabah Country, Malaysia. Indonesia has potential coffee and an opportunity ofexpanding coffee market in Sabah Country but this is inhibited with the enactmentof cabotage policy and the quota limitation of 60 tons in once import a yearencourage Republic of Indonesia’s Consulate General in Kinabalu City to useeconomic diplomacy to help Indonesian coffee employers. The authors employedeconomic diplomacy taken by government and employers in the theory. Theobjective of research was to find out the real manifestation of economicdiplomacy attempts taken by Republic of Indonesia’s Consulate General inKinabalu City as the Indonesian Government’s official representatives. Economicdiplomacy conducted by the Consulate General of the Republic of Indonesia KotaKinabalu is by representing the central government of the Republic of Indonesiaand promoting Indonesian coffee at international events held in the State ofSabah, negotiating with parties related to cabotage policy, and providing reportingto the government center and businessman. The research method employed wasqualitative one with primary and secondary data. Data collection was conductedusing interview and documentation methods and the data collected was analyzeddescriptively. From the result of research, it could be found that economicdiplomacy of Republic of Indonesia’s Consulate General in Kinabalu City incooperation with coffee employers and media could facilitate Indonesian coffeeemployers to expand coffee market in Sabah Country.Keywords: Economic Diplomacy, Republic of Indonesia’s Consulate General inKinabalu City